Redox interactions of methylene blue with cysteine amino acid as a possible mechanizm of biological action of the dye - Shelkovsky, V. S.; Kosevich, M. V.; Boryak, O. A.; Zobnina, V. G.; Plokhotnichenko, A. M. (Biophysical Bulletin, 1970)
Design of the inhibitors of the pathogenic protein aggregation, associated with the neural cell damage, is of great importance for the therapy of the neurodegenerative diseases. In this work redox interactions of methylene blue as a potential drug against Alzheimer’s disease with its potential target – cysteine of the active cite of Tau proteins, have been studied in vitro, in order to establish the molecular mechanism of methylene blue biological action. First, a single product of direct oxidation of cysteine by methylene blue, viz. cystine, possessing a disulfide bridge between two cysteine molecules, has been detected by mass spectrometry. Such modification of cysteine residues was suggested to affect secondary structure of Tau-proteins, hampering amyloid fibril formation. Notably, we failed to detect any oxygen-containing products of cysteine oxidation. Finally, reduction of methylene blue in the above reaction resulted in the formation of its leuco form, which could be also considered as a potential drug in the therapy of neurodegenerative diseases.